2014
DOI: 10.3168/jds.2013-7534
|View full text |Cite
|
Sign up to set email alerts
|

Association of digital cushion thickness with sole temperature measured with the use of infrared thermography

Abstract: The main objective of this study was to investigate the association between digital cushion thickness and sole temperature measured by infrared thermography. Data were collected from 216 lactating Holstein cows at 4 to 10d in milk (DIM). Cows were locomotion scored and sole temperature was measured after claw trimming (a minimum delay of 3 min was allowed for the hoof to cool) using an infrared thermography camera. Temperature was measured at the typical ulcer site of the lateral digit of the left hind foot. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
2
10
0
2
Order By: Relevance
“…In previous work that scanned the sole soft tissues within 4 to 10 d after calving, the soles of feet in cows without lesions were hotter if the sole soft tissues were thinner. The authors hypothesized that reduced sole soft tissue thickness was associated with trauma in the region and early signs of inflammation, before CHDL became visible (Oikonomou et al, 2014b); this thinness could have been predisposed by laxity of the suspensory apparatus. Such results could suggest that vascular or inflammatory changes occur within the soft tissues of the sole of the foot in lesion development.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work that scanned the sole soft tissues within 4 to 10 d after calving, the soles of feet in cows without lesions were hotter if the sole soft tissues were thinner. The authors hypothesized that reduced sole soft tissue thickness was associated with trauma in the region and early signs of inflammation, before CHDL became visible (Oikonomou et al, 2014b); this thinness could have been predisposed by laxity of the suspensory apparatus. Such results could suggest that vascular or inflammatory changes occur within the soft tissues of the sole of the foot in lesion development.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, the DNA concentration and 260/280 ratio were measured with a NanoDrop 1000 spectrophotometer (Nanodrop Technologies, U.S.), and integrity was visualized by running aliquots on an agarose gel. The V1-V2 region of the 16S rRNA gene was PCR-ampli ed by (GeneAmp 9700, ABI, U.S.) using forward (5'-CGTATCGCCT-CCCTCGCGCCATCAG-3') and reverse (5'-CTA-TGCGCCTTGCCAGCCCGCTCAG-3') primers that incorporated adaptors and barcodes [14,45]. Amplicons of about 450 bp were selected and combined in equal concentrations [46], then electrophoresed and extracted from the gel with GeneJET (ThermoFisher, Waltham, MA, United States).…”
Section: Bacterial Dna Isolated 16s Rrna Genes Ampli Ed and Sequencedmentioning
confidence: 99%
“…These authors concluded that measurement of foot temperature in early lactation may be useful for monitoring hoof health. Other studies measured the radiated temperature at the coronary band in cows without foot lesions, and demonstrated that there was no significant difference in surface temperature between left and right hind limbs but a significant difference in temperature when only one of these limbs was affected by a foot lesion [ 21 , 31 ]. Renn et al [ 32 ] were able to classify 139 lame cows out of 142 when detecting temperatures over 27 °C, when one foot at least was affected with lameness.…”
Section: Clinical Applicationmentioning
confidence: 99%